Aktivitas antibakteri ekstrak daun benalu Dendrophthoe pentandra pada tanaman Citrus microcarpa Bunge terhadap Mycobacterium smegmatis, Escherichia coli dan Salmonella typhi - Kanter, Jabes Wolter; Mongi, Jeane; Kalangi, Only Imando; Maarisit, Wilmar; Pareta, Douglas Natan; Sambou, Christel Natanael; Tulandi, Selvana S. (Journal of Pharmaceutical and Sciences, 2025)
Diseases caused by bacteria infections are renowned for hurting human health and may become fatal when not treated with appropriate medical therapy. Meanwhile, several bacteria, including Mycobacterium smegmatis, Escherichia coli, and Salmonella typhi, are resistant to numerous antibiotics. Therefore, this study aimed to find new compounds from plants with antibacterial potential. The results showed that based on phytochemical screening, Dendrophthoe pentandra mistletoe leaf on Citrus microcarpa Bunge plants had compounds with antibacterial activity, namely alkaloids, flavonoids, tannins, and phenolics. According to Gas Chromatography-Mass Spectrometry (GC-MS) analysis, eight compounds have antibacterial properties, namely 2-Myristynoyl pantetheine; 2H-Indeno[1,2-b]furan-2-one, 3,3a,4,5,6,7,8,8b-octahydro-8,8-dimethyl; Acetamide, N-methyl-N-[4-(3-hydroxypyrrolidinyl)-2-butynyl]-; Ethyl iso-allocholate; a-D-Glucopyranoside, methyl 2-(acetylamino)-2-deoxy-3-O-(trimethylsilyl)-, cyclic methylboronate; tert-Hexadecanethiol; Sarreroside; and d-Mannose. D. pentandra mistletoe leaf extract had a better effect or activity on inhibiting the growth of M. smegmatis than E. coli and S. typhi. It was concluded that D. pentandra mistletoe leaf on Citrus microcarpa Bunge plants had antibacterial activity.